Cardiorespiratory fitness, body mass index and heart failure incidence. (19th February 2019) - Kokkinos, Peter; Faselis, Charles; Franklin, Barry; Lavie, Carl J.; Sidossis, Labros; Moore, Hans; Karasik, Pamela; Myers, Jonathan
Abstract : Aims: Obesity is associated with increased risk of heart failure (HF). This risk may be modulated by improved cardiorespiratory fitness (CRF) as CRF is associated with favourable health outcomes. Thus, we assessed the interaction between body mass index (BMI), CRF and HF. Methods and results: Cardiorespiratory fitness and BMI were assessed in 20 254 US male veterans (mean age 58.0 ± 11.3 years), who completed a maximal exercise treadmill test between 1987 and 2017. All had no evidence of ischaemia or HF prior to the exercise test. They were classified based on age‐stratified quartiles of peak metabolic equivalents (METs) achieved as: least‐fit (4.5 ± 1.3), low‐fit (6.7 ± 1.3), moderate‐fit (8.1 ± 1.1), and high‐fit (11.2 ± 2.4); and according to BMI as normal weight (18.5–24.9 kg/m 2 ), overweight (25–29.9 kg/m 2 ), and obese (≥ 30.0 kg/m 2 ). During a median follow‐up of 13.4 years, there were 2979 HF events (10.8 events/1000 person‐years). HF risk was significantly higher in the obese category [hazard ratio (HR) 1.22, 95% confidence interval (CI) 1.10–1.36; P < 0.001], but was no longer significant after further adjustment for METs. When compared to the least‐fit, HF risk declined progressively with increased CRF within all BMI categories. The risk was 63% (HR 0.37, 95% CI 0.30–0.47; P < 0.001), 66% (HR 0.37, 95% CI 0.28–0.40; P < 0.001), and 73% (HR 0.27, 95% CI 0.22–0.34; P < 0.001) lower for high‐fit individuals within normal weight, overweight and obese categories, respectively. Conclusions: Increased CRF was associated with progressively lower HF risk regardless of BMI, suggesting that the elevated HF risk associated with obesity may be modulated by improved CRF.